Batch Adsorption Of Amoxicillin On Coconut Shell Activated Carbon - Zainal, Danial Syakirin (Universiti Sains Malaysia, 2022)
Due to its broad spectrum against a number of infections, amoxicillin is one of the most widely utilised commercial penicillin antibiotics. Their presence in the ecosystem may be linked to impending environmental issues. This study aims to examine the influence of adsorbent dosage, starting amoxicillin concentration, and temperature at a constant pH on the adsorption of amoxicillin onto activated carbon. This experiment determined the optimal batch conditions to be 10 mg/L initial amoxicillin concentration, 2 g adsorbent dose, and 50ºC. The effects of various parameters on the transfer of amoxicillin antibiotic between the aqueous phase and the organic phase were studied, and it was shown that the kinetic transfer process could be successfully modelled using the generic two-film theory of mass transfer to a flat interface. Using pseudo first-order and pseudo second-order models to examine the kinetics of amoxicillin adsorption onto coconut shell activated carbon indicated that amoxicillin adsorption followed a pseudo first-order kinetic model. Among the three examined models (Langmuir, Freundlich, and Temkin), the Langmuir model best described the amoxicillin adsorption isotherm. The thermodynamic parameters ΔGº, ΔH°, and ΔS° suggested that the adsorption of amoxicillin onto activated carbon derived from coconut shell was spontaneous and endothermic. In conclusion, coconut shell activated carbon was discovered to be an effective adsorbent for the removal of amoxicillin antibiotics from wastewater under a variety of situations.